The Forensic Construction Expert as a Mediator - A. Yu. Butyrin; E. B. Stativa; O. V. Zhukova; A. V. Kapustkina (Теория и практика судебной экспертизы)
The issue of out-of-court settlement of disputes between participants in construction is considered. The relevance of the study stems from the excessive number of legal disputes of business entities. This fact requires a new perspective on the existing but still unpopular conciliation procedures, which can mitigate the burden of the judiciary. The mediation procedure seems to be the most attractive to the authors to that end. The article provides a range of advantages of turning the disputants to the mediator in comparison with the traditional judicial process. In this regard, the attention of the authors is focused on the mediator figure itself, the benefits of engaging an expert builder (a person competent in the field of construction who carries out forensic analysis on a permanent basis) are explained.The question of whether the participants in the construction industry are ready to resolve their economic disputes in the pretrial order is considered. According to the authors this is obstructed by: persistent paternalism firmly entrenched in the minds of the disputing parties, traditional distrust to the mediator as not having the authority, the exhaustiveness of the parties’ desire for unquestionable victory in the dispute and not for a compromise the inefficiency of the defensive practice using concealment or falsification of information, etc.In conclusion, the authors note the current unreadiness of the construction industry parties to actively participate in out-of-court settlement of disputes as well as a positive tendency among the Russian builders to using civilized forms of industrial interaction and express the hope that mediation will take its rightful place in the segment of public relations under consideration.